1996
DOI: 10.1002/qsar.19960150304
|View full text |Cite
|
Sign up to set email alerts
|

New Analgesics Designed by Molecular Topology

Abstract: Molecular topology has been applied to the design of new analgesic drugs, utilizing linear discriminant analysis and connectivity functions using different topological descriptors. Of a total of 26 compounds selected, 17 showed analgesic activity. The following stood out particularly, showing analgesic values greater than 75% regarding ASA (acetylsalicylic acid), the reference drug: 2-( l-propenyl)phenol, 2'4' dimethylacetophenone, p-chlorobenzohydrazide, I-(p-chlorophenyl) propanol and 4-benzoyl-3-methyl-1 -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The molecular connectivity method is used to investigate the relationship between the experimental values of physical or biological properties and calculated connectivity indices [25,26] . In recent studies the usefulness of molecular connectivity has been demonstrated in the design of analgesics [27,28] . In this paper, some structural parameters (such as log P, parachor, molar refractivity, and molecular connectivity indices) were studied for possible correlation with antinociceptive activity of some 3(2H)-pyridazinone derivatives (Table 4 and Table 5).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…The molecular connectivity method is used to investigate the relationship between the experimental values of physical or biological properties and calculated connectivity indices [25,26] . In recent studies the usefulness of molecular connectivity has been demonstrated in the design of analgesics [27,28] . In this paper, some structural parameters (such as log P, parachor, molar refractivity, and molecular connectivity indices) were studied for possible correlation with antinociceptive activity of some 3(2H)-pyridazinone derivatives (Table 4 and Table 5).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Number of graph vertices.4 9 Vk, vertices of degree k, where k is 3 or 4. Number of vertices of degree k.4 9 R, ramification.…”
Section: Descriptorsmentioning
confidence: 99%
“…Number of vertices of degree k.4 9 R, ramification. Number of single structural branches.4 9 W, Wiener paths number. Sum of topological distances in the graph.5 3 L, length.…”
Section: Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations